2012
DOI: 10.1016/j.plantsci.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Some like it hot, some like it warm: Phenotyping to explore thermotolerance diversity

Abstract: Plants have evolved overlapping but distinct cellular responses to different aspects of high temperature stress. These responses include basal thermotolerance, short- and long-term acquired thermotolerance, and thermotolerance to moderately high temperatures. This thermotolerance diversity’ means that multiple phenotypic assays are essential for fully describing the functions of genes involved in heat stress responses. A large number of genes with potential roles in heat stress responses have been identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
172
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(178 citation statements)
references
References 144 publications
3
172
0
Order By: Relevance
“…Thus, it is important to determine whether decreased fruit and seed set by heat stress is due to source or sink limitation. Unlike severe heat stress, moderate heat stress generally has no detrimental effect on photosynthesis (Lafta and Lorenzen, 1995;Yeh et al, 2012;Hancock et al, 2014). Consistently, we found that LMHS adopted in this study also had no effect on the leaf photosynthesis and total plant biomass in either wild-type or transgenic tomato (Supplemental Fig.…”
Section: Cwin Promotes Fruit Set Under Lmhs By Increasing Sink Strengsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, it is important to determine whether decreased fruit and seed set by heat stress is due to source or sink limitation. Unlike severe heat stress, moderate heat stress generally has no detrimental effect on photosynthesis (Lafta and Lorenzen, 1995;Yeh et al, 2012;Hancock et al, 2014). Consistently, we found that LMHS adopted in this study also had no effect on the leaf photosynthesis and total plant biomass in either wild-type or transgenic tomato (Supplemental Fig.…”
Section: Cwin Promotes Fruit Set Under Lmhs By Increasing Sink Strengsupporting
confidence: 84%
“…However, compared to SSHS, longterm moderate heat stress (LMHS) is a more frequent event under field conditions especially amid gradually increasing temperature associated with climate change (Sato et al, 2006). The response mechanisms of plants to LMHS may be drastically different from those to SSHS (Yeh et al, 2012;Hancock et al, 2014). For example, mitochondrial cochaperone MGE2 is required for the tolerance of Arabidopsis vegetative growth to LMHS (35°C for 9 d), but not for its response to SSHS (44°C for 150 min; Hu et al, 2012;Yeh et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the roles of small RNAs in transcriptome homeostasis, cellular tolerance, phenological and developmental plasticity of plants under heat stress and recovery will help genetic engineering of stress tolerance in crop plants [90]. In addition, microarray technology has recently become a powerful tool for the systematic analysis of expression (or transcriptome) profiles of large numbers of genes those are induced or repressed by heat treatment [91,92]. Recent microarray studies in Arabidopsis deficient with APX gene, however, have found that certain HSPs are expressed typically under other stress conditions, although expression of HSPs under heat stress occurs normally [93].…”
Section: "Omics" Technologiesmentioning
confidence: 99%
“…In the HSA32 null mutant of Arabidopsis, acquired thermotolerance is normally attained after a short recovery of 2 h, following heat acclimation treatment at 37°C for 1 h, but is significantly compromised after a long recovery for 48 h . Based on this phenotype, acquired thermotolerance attained after a long recovery period was named longterm acquired thermotolerance (LAT), as opposed to the ordinary short-term acquired thermotolerance (SAT; Yeh et al, 2012). The heat-inducible heat shock transcription factor HSFA2 and a peptidyl-prolyl cis-transisomerase (ROF1) have also been shown to be involved in LAT but not SAT (Charng et al, 2007;Meiri and Breiman, 2009).…”
mentioning
confidence: 99%